Morphological Pattern of Endometrial Biopsies In South Western Nigeria. (2016)
Background: Endometrium remains the most sensitive indicator of ovarian function and endometrial biopsy is one of the diagnostic procedures in endometrial pathology. The current study was carried out to examine the morphological pattern of endometrial biopsies in Ibadan, South-western Nigeria and compare the results with similar studies. Method: A retrospective study was undertaken to review all cases of endometrial biopsies received in the Department of Pathology, University College Hospital, Ibadan between January 1999 and December 2008. The patients’ data were retrieved from the surgical pathology daybooks and Histology Request forms. The neoplastic lesions were classified according to 2003 World Health Organization classification for endometrial neoplasms. Results: A total of 2,444 cases of endometrial biopsies were received during the 10-year study period. The functional endometrial changes were the most common histopathological diagnostic category, accounting for 53.8% (1035) of cases. Other pathological diagnoses included endometritis (7.8%), simple endometrial hyperplasia (5.8%), partial hydatidiform mole (2.3%), complete hydatidiform mole (2.1%) and malignant neoplastic lesions (3.9%). Infertility was the most common (57%) indication for endometrial biopsies followed by uterine bleeding (33%) while the least common clinical indication were the menstrual disorders (10%). Conclusion: The functional endometrial changes account for the highest morphological patterns while malignant lesions account for the least pattern of the endometrial biopsies evaluated for etiological basis of infertility, uterine bleeding and menstrual disorders in Ibadan. Infertility was the commonest indication for endometrial biopsies while the least common clinical indication was menstrual disorders.